SPECTROPHOTOMETRIC DETERMINATION OF AN ANTIMALARIAL DRUG CHLOROQUINE IN BULK AND PHARMACEUTICAL FORMULATIONS - Karad, Manjusha D.; Barhate, V. D. (International Journal of Current Pharmaceutical Research, 2015)
Objective: The aim of this paper was to develop the spectrophotometric method of an antimalarial drug chloroquine in bulk and pharmaceutical formulations. Methods: A simple, sensitive and accurate spectrophotometric method have been developed for the determination of chloroquine in pure and dosage forms which is based on oxidation of the drug with Fe(III)-1, 10 phenanthroline complex producing orange colored chromogen which is measured at 510 nm. Different experimental parameters affecting the color development and stability of the colored product are carefully studied and optimized. Results: Beer's law is obeyed in the concentration range of 20-320 Âµg/ml for the developed method. The molar absorptivity and sandell sensitivity are found to be 666.66 L mol-1 cm-1 and 0.77 Âµg/cm2 respectively. The regression equation for chloroquine was found to be y = 0.0013X+0.005 and the correlation coefficient for the regression line were 0.999. Conclusion: The developed method could be successfully applied for determination of chloroquine in pharmaceutical formulations. The results obtained are in good agreement with those obtained by using the standard method.